2015
DOI: 10.1016/j.eururo.2014.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Nephron-sparing Techniques Independently Decrease the Risk of Cardiovascular Events Relative to Radical Nephrectomy in Patients with a T1a–T1b Renal Mass and Normal Preoperative Renal Function

Abstract: Background: Some reports have suggested that nephron-sparing surgery (NSS) may protect against cardiovascular events (CVe) when compared with radical nephrectomy (RN). However, previous studies did not adjust the results for potential selection bias secondary to baseline cardiovascular risk. Objective: To test the effect of treatment type (NSS vs RN) on the risk of developing CVe after accounting for individual cardiovascular risk. Design, setting, and participants: A multi-institutional collaboration includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(139 citation statements)
references
References 38 publications
(30 reference statements)
2
126
0
11
Order By: Relevance
“…13 Conversely, the European Organization for Research and Treatment of Cancer (EORTC) trial 30904 demonstrates that PN seems to be significantly less effective than RN in terms of overall survival and several studies reported a significantly higher postoperative complication rates of PN in complex renal masses and/or comorbid patients. 14 To date, the controversial opinions about the risk/benefit ratio of both PN and RN along with the clinical features of each patient often influenced the treatment decision for localized RCC.…”
Section: Discussionmentioning
confidence: 99%
“…13 Conversely, the European Organization for Research and Treatment of Cancer (EORTC) trial 30904 demonstrates that PN seems to be significantly less effective than RN in terms of overall survival and several studies reported a significantly higher postoperative complication rates of PN in complex renal masses and/or comorbid patients. 14 To date, the controversial opinions about the risk/benefit ratio of both PN and RN along with the clinical features of each patient often influenced the treatment decision for localized RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of the study was ESRD, defined as the onset of a postoperative estimated glomerular filtration rate (GFR) <15 ml/min per 1.73 m 2 . GFR was calculated by the Chronic Kidney Disease Epidemiology Collaboration formula in younger patients (aged <70 yr) and by the Berlin Initiative Study formula in older patients (aged 70 yr) [3]. We included the following covariates: age, year of surgery, preoperative GFR, tumor size, hypertension (none, uncontrolled, or controlled by medical therapy), diabetes, baseline Charlson comorbidity index (CCI), BMI, and smoking status (no, yes, or former).…”
mentioning
confidence: 99%
“…12 Considering, above all, the functional benefits and the comparable oncological outcomes over RN offered by NSS, partial nephrectomy has been therefore more widely adopted among urological centres. 13,14 In the present study, we evaluated the clinical, demographic, intraoperative and pathological data of those patients undergoing PN between 2009 and 2012 in 19 Italian Institutions. In this study, although the period considered is relatively short (4 years), asymptomatic patients were significantly higher in the second half of the evaluation period.…”
Section: Discussionmentioning
confidence: 99%